An Overview of Dc Electric Vehicle Chargers with Transformerless Capability - Espina-Gonzalez, E; Diaz-Diaz, M (Institute of Electrical and Electronics Engineers Inc., 2024)
There is a growing trend towards the mass adoption of Electric Vehicles (EVs), driving the need for advanced EV charging technology. EV chargers cover various modes and power ratios with the primary goal of reducing charging times. Fast electric vehicle chargers typically use direct current and require galvanic isolation, requiring multiple conversion stages that increase cost and complexity. Recently, transformerless DC chargers have been proposed as a cost-effective alternative that simplifies EV chargers by reducing the number of conversion stages. However, there are few articles on this topic. This paper provides a comprehensive overview of electric vehicle chargers, with a particular focus on fast charging technology, standards, and regulations. Special attention is given to transformerless technology, describing topologies and key control strategies to highlight its potential advantages in EV charging applications. © 2024 IEEE.